The Relationship Between Work Shift, Work Load and Age on Work Stress in Employees at PT. X Batam City in 2024 - Jamal, Jamal; Kafit, M.; Jayati, Trisna; Mariana, Mariana (Rifa'Institute, 2025)
Introduction: Work stress is a common issue in the workplace and can be triggered by various factors such as irregular work shifts, employee age, and excessive workloads. Irregular shift changes may disrupt employees' rest periods, while age can influence stress levels, with older employees generally more prone to experiencing work-related stress. Long working hours and high workload demands also contribute significantly to the development of work stress. Objective: This study aims to examine the relationship between work shifts, age, and workload with work stress among employees at PT. X in Batam City. Method: A quantitative research method with a cross-sectional approach was employed. Data were collected using questionnaires and observation sheets. The chi-square test was used for statistical analysis. Results and Discussion: The findings revealed significant relationships between work shifts and work stress (P = 0.002), workload and work stress (P = 0.040), and age and work stress (P = 0.023). These results indicate that the examined variables contribute to the levels of stress experienced by employees. Conclusion: It is recommended that PT. X improve employee welfare by regulating rest periods, minimizing sudden shift changes, and reducing excessive workloads to create a safer, more comfortable, and productive work environment.